POLA JARINGAN KOMUNIKASI MASYARAKAT MISKIN untuk PROGRAM-PROGRAM PENANGGULANGAN KEMISKINAN (ANALISIS JARINGAN KOMUNIKASI DI DUKUH TEGAL MIRING, DESA LUWEH, KABUPATEN SEMARANG) - Tandiyo Pradekso (Faculty of Social and Political Sciences, Universitas Diponegoro, 2009)
The research mainly argues that there are communication and socialization problems in the goverment’s programs in decreasing the rate of poverty in Indonesia. Using communication network analysis, this research indicate that the communication network’s pattern’s of three poverty related programs (BLT, Raskin, and Askeskin) are centralized in nature. The centralized pattern means a lact of dyadic communications which relates to the low communication gratification for the networks members. The society disappointment and distrust to the programs is also caused by the low quality of data collection about poor households and lack of honest communication of the officers who are involved to the programs.